2011
DOI: 10.1088/0029-5515/51/10/103006
|View full text |Cite
|
Sign up to set email alerts
|

Integrated modelling of steady-state scenarios and heating and current drive mixes for ITER

Abstract: Recent progress on ITER steady-state (SS) scenario modeling by the ITPA-IOS group is reviewed. Code-to-code benchmarks as the IOS group's common activities for the two steady state scenarios (weak shear scenario and internal transport barrier scenario) are discussed in terms of transport, kinetic profiles, and heating and current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 32 publications
1
49
0
Order By: Relevance
“…It was found that the overall results from different codes using the stiff theory-based (GLF23) model agree well. 6 There are still some discrepancies in the fusion products and, as mentioned before, differences in the computed loss mechanism (such as radiation). Global and local current balance is important for steady state scenarios.…”
Section: -16mentioning
confidence: 95%
See 2 more Smart Citations
“…It was found that the overall results from different codes using the stiff theory-based (GLF23) model agree well. 6 There are still some discrepancies in the fusion products and, as mentioned before, differences in the computed loss mechanism (such as radiation). Global and local current balance is important for steady state scenarios.…”
Section: -16mentioning
confidence: 95%
“…Simulations have been performed limited to the evolution of current and temperatures (i.e., with non-evolving density, rotation and impurity profiles). This benchmark exercise was extended to steady-state scenarios, 6 one characterised by high pedestal and weak shear, and a second study with ITB. The results of the benchmarks for the hybrid and steady-state scenarios are summarized here.…”
Section: Benchmarking Hybrid and Steady-state Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling between the core transport solver and the external components usually occurs at memory level in view of the frequent calls that the core solver has to make to its modules while integrating the transport equations in time. A non-exhaustive list of these codes are ONETWO [1,2], TRANSP/PTRANSP [3], TOP-ICS [4], ASTRA [5], CRONOS [6], CORSICA [7], FAS-TRAN [8], FACETS [9].…”
Section: Transport-based Frameworkmentioning
confidence: 99%
“…Previous work on steady-state exploration in ITER with internal transport barriers includes integrated benchmark of transport codes by Kessel et al 13 and Murakami et al, 18 steady state scenarios by Garcia et al 16,19 (who also extensively discuss the role of reverse shear) and Giruzzi et al 20 In this work, we examine the formation of ITBs in L-mode and their sustainment in the flattop phase with the day-one heating mix. We discuss, in particular, how the electron cyclotron (EC) launcher configuration affects the magnetic geometry and the dynamics of ITBs.…”
Section: Introductionmentioning
confidence: 99%